Power/knowledge and space : the creation and alienation of the "reserve" at Porirua : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Geography at Massey University - McClean, Robert Andrew (Massey University, 1996)
Maps are common images in society. With the help of a map stories are told, histories are written, the weather is forecast, cities are planned and countries are defined. Usually the map presents a view-point from a position of a birds-eye perspective; a view looking down on 'us' from somewhere above, a vision that can see 'everything'. In this thesis I take a critical 'look' at the map and investigate how the map creates ideas of space and place. Instead of a 'mirror' of reality, I will argue the map is a 'text' produced within a discursive formation and within this formation, mapping discourse presents a representation of social realities. The map as a discourse also has an ideological role as the spaces on the map are used to reproduce unequal social relationships. In exploring the map as ideological discourse, I will illustrate how the map has been used by colonialism and imperialism to produce an'Empire'. Thus, imperialism is a social process that creates space (or territory) and invades that space with the help of mapping discourse. Imperialism derives its power by the use of knowledges that defines the 'Other' in a cartographical space. Mapping discourse played a critical role in the creation of Porirua as a 'district' and in the alienation of the district after the arrival of New Zealand Company settlers in 1840. With the aims of acquiring Porirua for 'settlement' and for the intention of amalgamating Toa Rangatira into 'civilization', three reserves were created with a map in 1847. Later in the 1860s, with the arrival of more settlers from Europe, the surveyors attempted to make the reserves 'disappear' in an effort to individualize the collective lands of Toa Rangatira. This process of cartographical fragmentation was, and still is, contested by Toa Rangatira. However, rather than provide a space for the amalgamation of the tribe into European society, the remnants of the original reserves have become sites of resistance; places where Toa Rangatira can 'stand' together as an indigenous people. This resistance may also influence the re-emergence of small spaces of the original reserves as part of the Waitangi Tribunal claims process. In order to integrate my own positionality (way of seeing) into this thesis and make it more readable, I have organized the text around an extended metaphor of the tikouka (cabbage tree). Accordingly readers are encouraged to approach this thesis as if you are entering various rooms in a gallery, as opposed to reading the chapters in a traditional linear fashion. With the use of this metaphor, I want to give the impression that, like a tree, this thesis is grounded and situated in the political and social relations of place and time.
Keywords: Land tenure -- New Zealand; Porirua -- History; Maori (New Zealand people); Ngāti Toa (New Zealand people) -- Land tenure